Implementasi Bimbingan Karir dan Kegiatan Keterampilan dalam Memutuskan Karir Warga Binaan Lapas Kelas IIB Lamongan - Febriani, Risilva Aulia; Winingsih, Evi (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to describe the implementation of career guidance and skills training activities in assisting incarcerated adolescents at the Class IIB Lamongan Correctional Institution in making career decisions. The research employed a descriptive qualitative approach using purposive sampling. The research subjects consisted of five incarcerated adolescents who actively participated in career guidance and skills training programs. Data were collected through semi-structured interviews, field notes, and supporting documentation, and were analyzed narratively and in depth to explore the participants’ experiences, perspectives, and career decision-making processes. The findings indicate that career guidance plays an important role in helping incarcerated adolescents understand their personal potential, identify work interests, and gain insight into possible career options after completing their correctional program. Skills training activities provide practical competencies that enhance self-confidence and work readiness among the participants. Through the integration of career guidance and skills training, incarcerated adolescents begin to develop clearer career directions and make more informed career decisions. This study concludes that career guidance and skills training are essential components of the rehabilitation process for incarcerated adolescents, supporting their career readiness and post-release career decision-making.